Fracture features of anisotropic materials at different impact velocities*. Issue 5 (2nd November 2017) - Krivosheina, M. N.; Kobenko, S. V.; Tuch, E. V.; Kashin, O. A.; Lotkov, A. I.; Khon, Yu. A
Abstract: The paper provides a 3D finite element simulation to investigate the fracture of low-anisotropy aluminium alloy 2024 loaded by a steel impactor at a velocity of 200 and 600 m/s. For aluminium alloy 2024 a failure criterion in terms of ultimate plastic strains is used taking into account the elastic, plastic, and strength anisotropy of the target material. The simulation results, presented as cross-sectional fracture distributions, demonstrate that increasing the impact velocity results in additional fracture zones in anisotropic materials whose elastic, plastic, and strength properties are lowest in the in-plane direction compared to isotropic materials.